MNC implementation in health security - Achmad Singgih Laksono; Renitha Dwi Hapsari (Enrichment : Journal of Management, 2023)
The high number of morbidity and mortality, from the community and health workers due to COVID-19 in Indonesia. Create anxiety and worry in society. So that Indonesia seeks to overcome the spread of COVID-19, through restrictions on every community activity. Health services through the use of information and communication technology in the form of telemedicine, is one solution to deal with COVID-19.A calamity of the COVID-19 outbreak that hit Indonesia has induced an imbalance within the fitness protection of its human beings. In minimizing this, what is within the u . S . Have to strive as a good deal as feasible to assist repair the state of affairs, including multinational groups of their implementation, implementing CSR to repair fitness security. According to Archie Carroll, there are 4 pillars of CSR, namely philatropic obligation, ethical duty, prison obligation and monetary responsibility. Unilever is one of the MNCs that has product believe from the general public. Apart from products that help fitness, Unilever also often conducts community empowerment sports regarding maintaining health. Unilever does now not remain silent about COVID-19 that has hit Indonesia, Unilever implements CSR philanthropic obligation by donating products and budget to assist human beings restore desire for recuperation, empowering people to construct new mindsets and building infrastructure to help communities to comprehend fitness security sustainable. After approximately 2 years till COVID-19 become declared over, Unilever has succeeded in changing people's habits to come to be greater independent and feature exact behavior in preserving health.